La religione una risorsa formativa? - Nanni, Carlo (Studi sulla Formazione/Open Journal of Education, 2012)
The text aims to show how religion can contribute to the achievement of the human person. Religion, connected to the social and cultural framework, joins the individual world in its complexity. Is godlinesses a possible teaching resource? Yes, when read according to a pedagogical perspective, which support human advancement, historical and cultural being. The dialogue, good practice for any learning, it poses as a means to fight the life fragmentation in the discovery of common traces to all humanity.